Acute Hepatic Porphyria: Pathophysiological Basis of Neuromuscular Manifestations - de Souza, Paulo Victor Sgobbi; Badia, Bruno de Mattos Lombardi; Farias, Igor Braga; Pinto, Wladimir Bocca Vieira de Rezende; Oliveira, Acary Souza Bulle (Frontiers in Neuroscience, 2021)
Acute Hepatic Porphyria represent a rare, underdiagnosed group of inherited metabolic disorders due to hereditary defects of heme group biosynthesis pathway. Most patients have their definite diagnosis after several years of complex and disabling clinical manifestations and commonly after lifethreatening acute neurovisceral episodes or severe motor handicap. Many key studies in the last two decades have been performed and led to the discovery of novel possible diagnostic and prognostic biomarkers and to the development of new therapeutic purposes, including small interfering RNA-based therapy, specifically driven to inhibit selectively delta-aminolevulinic acid synthase production and decrease the recurrence number of severe acute presentation for most patients. Several distinct mechanisms have been identified to contribute to the several neuromuscular signs and symptoms. This review article aims to present the current knowledge regarding the main pathophysiological mechanisms involved with the acute and chronic presentation of Acute Hepatic Porphyria and to highlight the relevance of such content for clinical practice and in decision making about therapeutic options.